Chapter 3 Race and Racial Thinking - David Eller, Jack (Taylor & Francis, 2015)
Knowledge of and sensitivity toward diversity is an essential skill in the contemporary United States and the wider world. This book addresses the standard topics of race, ethnicity, class and gender but goes much further by engaging seriously with issues of language, religion, age, health and disability, and region and geography. It also considers the intersections between and the diversities within these categories. Eller presents students with an unprecedented combination of history, conceptual analysis, discussion of academic literature, and up-to-date statistics. The book includes a range of illustrations, figures and tables, text boxes, a glossary of key terms, and a comprehensive bibliography. Additional resources are provided via a companion website.